2015
DOI: 10.3892/ol.2015.3186
|View full text |Cite
|
Sign up to set email alerts
|

Novel long non-coding RNA RP11-119F7.4 as a potential biomarker for the development and progression of gastric cancer

Abstract: Abstract. Long non-coding RNAs (lncRNAs) have been reported to be involved in gene dysregulation in numerous different types of cancer, and have subsequently emerged as a major series of regulatory molecules that participate in a broad range of biological and pathological processes. However, the correlation between the expression levels of lncRNAs and their clinical significance in gastric cancer remains unclear. The aim of the present study was to investigate the potential correlation between lncRNA RP11-119F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of short noncoding RNA molecules, which regulate and degrade approximate one‐third of the protein‐coding mRNAs and directly or indirectly influence almost all cellular pathways (Sun et al, ). Recently, the number of miRNA expression profiling studies has increased rapidly.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of short noncoding RNA molecules, which regulate and degrade approximate one‐third of the protein‐coding mRNAs and directly or indirectly influence almost all cellular pathways (Sun et al, ). Recently, the number of miRNA expression profiling studies has increased rapidly.…”
mentioning
confidence: 99%
“…The biogenesis and functions of lncRNAs and their roles in cancer have been recently reviewed . Aberrantly expressed lncRNAs have also been detected in GC and proposed as putative novel GC biomarkers …”
Section: Long Noncoding Rnas (Lncrnas) In Gcmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Aberrantly expressed lncRNAs have also been detected in GC and proposed as putative novel GC biomarkers. [30][31][32][33][34][35] In an attempt to identify oncogenic lncRNAs in GC, Huang et al 36 used RNA sequencing to characterize nine GC and matched normal tissues, as well as GC and noncancer cell lines. They focused on the highly upregulated lncRNA RP3-416H24.1 (KRT7-AS), which is an antisense RNA transcribed from the negative strand of the keratin 7, type II protein-coding gene (KRT7).…”
Section: Long Noncoding Rnas (Lncrnas) In Gcmentioning
confidence: 99%
“…Some recent reports have demonstrated that lncRNAs play a critical role in cancer development and progression and that they have the potential to serve as diagnostic and prognostic biomarkers in gastric cancer [15], prostate cancer [16], and hepatocellular carcinoma [17], among other cancers. LncRNAs are tumor-specific and are also very stable in serum, urine and other easily obtainable body fluids [18], which indicates that they are good candidate tumor biomarkers.…”
Section: Introductionmentioning
confidence: 99%